The Political and Military Dimensions of Countering Extremism in West Africa: A Study of Nigeria - Lawal, Ibrahim Ismail Lawal; Sanusi, Muhammad Lawal Sanusi; Musa, Ibrahim Musa (African Journal of Stability and Development (AJSD), 2025)
This article examines Nigeria's military and political strategies in countering Boko Haram, a significant threat to national and regional security. The rise of Boko Haram has posed complex challenges, necessitating a multifaceted response that encompasses both military operations and political reforms. The military strategies employed include counterinsurgency operations, the establishment of the Multinational Joint Task Force (MNJTF) for regional cooperation, and intelligence gathering through community engagement. While these efforts have led to territorial recovery and operational gains against Boko Haram, persistent violence and the group's resilience highlight critical shortcomings, including intelligence failures and troop morale issues. On the political front, the Nigerian government has recognised the importance of governance reforms and humanitarian assistance in addressing the root causes of extremism. However, challenges such as corruption, inadequate humanitarian responses, and limited reintegration programmes for former combatants hinder effective implementation. This article argues that a holistic approach combining military action with meaningful political reforms is essential for sustainable counter-extremism efforts. Strengthening intelligence capabilities, improving military logistics, and fostering community trust are crucial steps toward enhancing operational effectiveness. Ultimately, achieving lasting peace and stability in Nigeria requires addressing both immediate security concerns and the socio-economic grievances that fuel radicalisation. This study contributes to the discourse on counter-terrorism in West Africa by providing insights into Nigeria's unique challenges and opportunities in combating violent extremism.